Analisa dan Perancangan Sistem Monitoring Inventory Berbasis Website dengan Metode Rapid Application Development - Djaksana, Yan Mitha (SENTRI: Jurnal Riset Ilmiah, 2025)
Inventory management systems are an essential part of a company’s operational activities, serving as a control mechanism for product availability to ensure that business processes run efficiently and effectively. The rapid development of information technology has led companies to shift from manual to computerized inventory systems to enhance data accuracy, speed, and accessibility. This study aims to analyze and design a web-based inventory monitoring system for CV Murijaya Karya Teknik, a company that still relies on manual methods for managing product stock, recording incoming and outgoing goods, and generating reports. The research adopts the Rapid Application Development (RAD) methodology, which emphasizes fast system development with active user involvement throughout the process. The RAD approach consists of several stages: requirement planning, system design, construction and feedback, and implementation. Data were collected through observation, interviews, and documentation to determine user needs and system functionality. The proposed system is developed using PHP and MySQL with a structured design that includes database architecture, user interfaces, and inventory monitoring modules. The implementation of this system helps users easily record, process, and monitor stock data in real time while reducing errors caused by manual data handling. The results indicate that the web-based inventory monitoring system significantly improves the efficiency and accuracy of inventory management processes at CV Murijaya Karya Teknik. This study concludes that applying web-based technology and RAD methodology can be an effective solution for improving company performance and decision-making in inventory management.